METHODOLOGICAL BACKGROUND FOR INTERDISCIPLINARY TERMINOLOGY BILATERAL INTERPRETING TRAINING - Гурєєва, Л. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The article is dedicated to the modern problems of training of bilateral interpreting of interdisciplinary terminology. The author examines the process of formation of educational standards in Ukraine and abroad. The analysis of professional competence of a higher education professional is conducted. Based on a number of works of domestic and foreign researchers, the elements of translation competence are defined. The purpose of the article is to study the background, goals and content of the bilateral interpreting of interdisciplinary terminology. The concept of professional competence of an interpreter and its components is considered in detail. The goals and content of training of bilateral interpreting of interdisciplinary terminology at the final stage of the undergraduate program are determined. In order to specify the goals and content of the bilateral interpreting of interdisciplinary terminology training, the content of credit modules on the practice of interpreting, as well as their purpose and goals, in a number of leading Ukrainian universities is further explored. The conducted analysis of scientific and methodological documentation proves that sufficient attention is devoted to the formation of bilateral interpreting skills, but not to the formation of the professionally oriented lexical competence, which requires knowledge of the basic science and technology terminology. This proves the importance of studying interdisciplinary terminology in the process of bilateral interpreting training. The methods of research include the critical analysis of domestic and foreign literary sources and scientific observation. The result of the research is a theoretical analysis, which contributed to the definition of the goals and content area of bilateral interpreting of interdisciplinary terminology, considered within the framework of the defined components of the subject and procedural aspects of the abovementioned content area.